Regioexhaustive Functionalization of the Carbocyclic Core of Isoquinoline: Concise Synthesis of Oxoaporphine Core and Ellipticine - Horváth, Dániel Vajk; Domonyi, Frigyes; Palkó, Roberta; Lomoschitz, Andrea; Soós, Tibor (Synthesis, 2018)
A general and versatile strategy has been developed for the functionalization of the carbocyclic core of the isoquinoline. This regioexhaustive approach employs electrophilic halogenation as a toolbox methodology and delivers highly decorated intermediates that can be further elaborated toward medicinally relevant building blocks or natural products.
Keywords: isoquinoline; regioexhaustive; cross-coupling; heterocycles; fused-ring systems; ellipticine